Shaping and interpretation of Dpp morphogen gradient by endocytic trafficking. - Sheida Hadji Rasouliha; Gustavo Aguilar; Cindy Reinger; Shinya Matsuda (PLoS Genetics, 2025)
Dpp/BMP is a morphogen that controls the patterning and growth of the Drosophila wing disc. Although endocytic trafficking has been proposed to influence both extracellular Dpp distribution and signaling, how this process shapes and interprets the Dpp gradient under physiological conditions remains unclear due to limitations in visualizing endogenous Dpp. Here, we generated fluorescent protein-tagged functional dpp alleles that allow simultaneous visualization of extracellular and intracellular Dpp distributions. Using these tools, we found that, while Dynamin-mediated internalization is required for Dpp signaling activation, Rab5-mediated early endosomal trafficking is dispensable for Dpp spreading and signaling initiation but is required for signal termination by promoting the downregulation of activated receptors. We show that Dpp signaling is terminated at the multivesicular body (MVB), likely through ESCRT-dependent sorting of activated receptors into intraluminal vesicles (ILVs), rather than via Rab7-mediated lysosomal degradation. Notably, blocking MVB formation expanded the Dpp signaling gradient without altering the extracellular Dpp gradient, thus compromising extracellular Dpp gradient interpretation. Together, our findings reveal that the extracellular Dpp gradient is shaped by Dynamin-dependent internalization and interpreted through the duration of intracellular signaling.